Extraction and Optimization of Oil from Moringa Oleifera Seed as an Alternative Feedstock for the Production of Biodiesel - Abdulkareem, A.S.; Uthman, H.; Afolabi, A.S.; Awenebe, O.L. (IntechOpen, 2011)
None